"Policy Framework, Governance and Institutional Strategies in Indian Foreign Policy: Challenges and Opportunities in a Changing Global Order" - Dr. Pravita Tripathi, Dr. Balasaheb Chandraprakash Kilche, Dr. Khyatimaya Tripathy, Satyendra Gupta, Dr. Pradeep Tripathi, Dr. Namo Narayan, Shirish Shrikant Waghmare (Journal of Daoist Studies, 2026)
Indian foreign policy, while identifying key challenges and opportunities in the contemporary geopolitical landscape. Moving beyond traditional non-alignment, India has adopted a pragmatic multipolar approach, emphasizing issue-based partnerships and balanced engagement with major powers, including the United States, Russia, China, and Europe. Key institutional strategies include the role of the National Security Council (NSC), modernization of the Ministry of External Affairs, and active participation in multilateral platforms such as the G20, BRICS, and the Shanghai Cooperation Organisation (SCO). However, India faces several challenges: strategic competition in the Indo-Pacific due to China’s rise, global issues like energy security and climate change, and obstacles in securing a permanent seat on the UN Security Council. Domestically, constraints include limited resources, bureaucratic delays, and a lack of coordination in foreign policy formulation. On the opportunities front, India’s growing economic strength, digital diplomacy, and leadership role in the Global South position it as an emerging global power. Initiatives such as the G20 presidency and the New Delhi Declaration have reinforced India’s diplomatic reach and soft power. In conclusion, the success of India’s foreign policy lies in balancing strategic autonomy with functional partnerships, strengthening institutional capacities, and articulating a clear global vision that aligns national interests with international responsibilities. Effective public governance requires an integrated policy framework that aligns institutional structures with strategic objectives to deliver sustainable and inclusive outcomes. The OECD Policy Framework on Sound Public Governance provides governments with a diagnostic and benchmarking tool to improve governance quality, emphasizing key values like transparency, accountability, responsiveness, efficiency, equity, and rule of law . A robust policy framework encompasses three interconnected dimensions. First, governance structures establish the leadership model, decision-making processes, and accountability mechanisms that guide policy implementation. These structures build partnerships across sectors and promote community leadership while ensuring mutual accountability . Second, policy instruments include management tools and regulations that enhance policy-making quality at different stages of the policy cycle, from formulation to evaluation. Third, institutional arrangements define the roles of ministries, local governments, communities, and civil society,legitimizing their participation in governance processes . Institutional strategies must address capacity development at multiple levels. Good governance rests on principles that require investing in human resources through competitive salaries, career prospects, and capacity building that facilitates informed decision-making . Anti-corruption frameworks are essential to incentivize policy decisions in the public interest, constraining coordination between bribe-takers and bribe-givers while employing behavioral nudges and emphasizing reputational risks . Transparency and accountability form the cornerstone of effective institutional strategies. Opening data about government operations enables external scrutiny and evidence-based policy decisions . Engaging official monetary institutions like anti-corruption bureaus and Supreme audit institutions, alongside civil society, supports both corruption monitoring and inclusive decision-making . The framework also emphasizes reducing policy errors through structural reform, automation, and improved rules that limit discretion where clear cases for government intervention don exist . When intervention is necessary, policy decisions can be outsourced or automated to perform better than corrupt manual processes . Strategic self-assessment questions help policy-makers evaluate institutional and decision-making capacity in key public governance areas, ensuring reforms pursue successful outcomes . This multidimensional approach is particularly critical as governments manage crises and plan for sustainable recovery, requiring coherent governance that integrates values, enablers, and management tools .Ultimately, sound public governance depends on aligning policy frameworks with institutional capacities while maintaining continuous monitoring, inclusive engagement, and adaptive strategies that respond to interconnected challenges of contemporary governance .